Characterization of an apparently synonymous F5 mutation causing aberrant splicing and factor V deficiency. (3rd December 2014) - Nuzzo, F.; Bulato, C.; Nielsen, B. I.; Lee, K.; Wielders, S. J.; Simioni, P.; Key, N. S.; Castoldi, E.
Summary: Coagulation factor V (FV) deficiency is a rare autosomal recessive bleeding disorder. We investigated a patient with severe FV deficiency (FV:C < 3%) and moderate bleeding symptoms. Thrombin generation experiments showed residual FV expression in the patient's plasma, which was quantified as 0.7 ± 0.3% by a sensitive prothrombinase‐based assay. F5 gene sequencing identified a novel missense mutation in exon 4 (c.578G>C, p.Cys193Ser), predicting the abolition of a conserved disulphide bridge, and an apparently synonymous variant in exon 8 (c.1281C>G). The observation that half of the patient's F5 mRNA lacked the last 18 nucleotides of exon 8 prompted us to re‐evaluate the c.1281C>G variant for its possible effects on splicing. Bioinformatics sequence analysis predicted that this transversion would activate a cryptic donor splice site and abolish an exonic splicing enhancer. Characterization in a F5 minigene model confirmed that the c.1281C>G variant was responsible for the patient's splicing defect, which could be partially corrected by a mutation‐specific morpholino antisense oligonucleotide. The aberrantly spliced F5 mRNA, whose stability was similar to that of the normal mRNA, encoded a putative FV mutant lacking amino acids 427–432. Expression in COS‐1 cells indicated that the mutant protein is poorly secreted and not functional. In conclusion, the c.1281C>G mutation, which was predicted to be translationally silent and hence neutral, causes FV deficiency by impairing pre‐mRNA splicing. This finding underscores the importance of cDNA analysis for the correct assessment of exonic mutations.